A Systematic Literature Review: The Trends and Challenges of AI (Chat GPT) for Reading Skills in ELT/L using The HHH Framework - Syafruddin, Syafruddin; Hidayati, Sari; Triastuti, Anita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study highlights the role of Artificial Intelligence (AI), particularly ChatGPT, in supporting the teaching of reading skills within the context of English Language Teaching and Learning (ELT/L). The primary focus of this research is on how the Helpful, Honest, Harmless (HHH) framework can be utilized to evaluate the trends and challenges of using AI in reading instruction. Based on a literature analysis, AI, especially ChatGPT, demonstrates significant potential to enhance reading skills through personalized learning approaches, active interaction, and immediate feedback. However, challenges such as algorithmic bias, limited access to technology, and risks of inappropriate content remain significant concerns. The HHH framework provides guidelines to ensure AI is effectively used to support beneficial, trustworthy, and safe learning processes. This study also offers recommendations to improve the responsible development and implementation of AI in the context of ELT/L education. Keywords: ChatGPT, Artificial Intelligence, Reading Skills, ELT/L, HHH Framework.